Fear of hypoglycemia in children with type 1 diabetes and their parents: Validation of the Italian version of the Hypoglycemia Fear Survey for Children and for Parents. Issue 1 (19th December 2021) - Tumini, Stefano; Fioretti, Elisabetta; Rossi, Ilaria; Cipriano, Paola; Franchini, Simone; Guidone, Paola Irma; Petrosino, Marianna Immacolata; Saggino, Aristide; Tommasi, Marco; Picconi, Laura; Gonder‐Frederick, Linda
Abstract: Background: Currently, Italian versions of the Hypoglycemia Fear Survey for Children (CHFS) and for Parents (PHFS) quantifying Fear of Hypoglycemia (FoH) in pediatric diabetes are not available. Objective: To validate the Italian version of the CHFS and PHFS. Subjects and methods: One hundred and seventy‐four children with type 1 diabetes aged 6–18 and 178 parents completed the CHFS and PHFS, the PedsQL 3.0 Diabetes module and the KIDSCREEN‐10. Internal consistency was good ( α = 0.85 for CHFS, α = 0.88 for PHFS); validity was supported by correlations of CHFS total score (CHFS‐T r = −0.50; p < 0.001, CI = ‐0.62 to −0.35) and Worry subscale (CHFS‐W r = −0.49; p < 0.001, CI = −0.62 to −0.32) with measures of health‐related quality of life (QoL), which were not related to PHFS scores. Factor analyses justified the structure and the separate scoring of Behavior and Worry subscales. Children's age was negatively correlated with CHFS‐T ( r = −0.16; p = 0.03, CI = −0.36 to 0.00), CHFS‐W ( r = −0.29; p = 0.02, CI = −0.39 to −0.07), PHFS‐T ( r = −0.20; p = 0.006, CI = −0.35 to −0.04), PHFS‐B ( r = −0.30; p = 0.001, CI = −0.43 to −0.17). Mean (SD) item scores of CHFS‐T (1.47 ± 0.56 vs. 1.27 ± 0.57; p < 0.05) and CHFS‐W (1.20 ± 0.73 vs. 0.96 ± 0.68; p < 0.05) were higher in children with HbA1c ≥7.5%. Higher levels of distress for upsetting hypoglycemia were associated with lower child's QoL scores as perceived by children (Peds‐QL: 72.6 ± 12.8 vs. 80.4 ± 11.9; p < 0.001) and parents (Peds‐QL: 70.6 ± 13.8 vs. 75.8 ± 12.9; p < 0.05). Conclusion: The Italian version of CHFS and PHFS appears to be a valid measure to assess FoH in clinical practice and factor analysis supports separate scoring for the Worry and Behavior subscales.